Chenchus of the forests and plateaux - Bhowmick, P.K. (Calcutta, 1992)
Among the Primitive continuing through recent times in this country, the Chenchus of Andhra Pradesh have come to occupy a very important position in the anthropological literature since the publication of the mono graph on them by Professor C. V. Fuerer Haimendorf. We have traversed a long way from the days of von Fuerer-Haimendorf's study and shall have to re-examine the way of life of these people, the changes therein and identify the factors responsible for such changes to see where these people fit in the democratic set up of our welfare state. Attempts have. been made here to have an in-depth study of the way how the Chenchus share with us the Indian civilisation through various historical processes of stressess and strains. The work will. hopefully, allay the fear of separatism and contribute in a substantial measure to our national integration. Details of ethnography along with the various measures for development of the tribe in recent times have been dealt with critically.
Keywords: Chenchus